Research on the Reasonable Width of the Waterproof Coal Pillar during the Mining of a Shallow Coal Seam Located Close to a Reservoir - Mengling Hu; Wenlong Zhao; Zheng Lu; Jianxi Ren; Yanping Miao (Advances in Civil Engineering)
Retaining a waterproof coal pillar is the most effective water conservation method for coal seam mining close to a reservoir, and determining a reasonable width for the waterproof coal pillar has been a common problem among mining scholars for a considerably long time. In case of mining a 4−2 coal seam close to the Changjiagou Reservoir in the Zhangjiamao mine, the research methods of theoretical analysis, physical simulation using similar materials, and numerical simulation have been adopted to analyze the overburden strata mining failure features and the surface subsidence law. Additionally, the influences of the width of the coal pillar on the reservoir bank slope stability have been investigated. The results denote that a coal pillar can be divided into a mine-pressure-influenced zone, an effective waterproof zone, and a water-level-influenced zone with respect to water resistance. Furthermore, the width of the waterproof coal pillar was determined to be 107.41 m by theoretical analysis. The simulation test indicated that when the working face advanced close to the reservoir, the reservoir bank exhibited vertical downward as well as transverse abscission layer fractures and the divided topsoil slipped toward the reservoir. Subsequently, the judgment conditions required for determining the critical width of the waterproof coal pillar were proposed based on the requirements to prevent the reservoir bank slope from instability failure and the water gushing accident in goaf. The maximum width of the waterproof coal pillar when the top point on the slope surface experienced reverse horizontal displacement and several key points produced sharp vertical displacements or when the pore pressure in the coal seam roof and floor suddenly became 0 was considered to be the critical width. Furthermore, the critical width was determined to be 96 m via simulation analysis, verifying the rationality of the theoretical method. These results could provide a theoretical basis for determining the width of the waterproof coal pillar of the coal seam located close to a reservoir.